2014
DOI: 10.1002/vnl.21422
|View full text |Cite
|
Sign up to set email alerts
|

High‐density polyethylene/natural rubber blends filled with thermoplastic tapioca starch: Physical and isothermal crystallization kinetics study

Abstract: High‐density polyethylene/natural rubber (HDPE/NR) blends filled thermoplastic tapioca starch was studied. In this blend system, thermoplastic starch (TPS) acted as an inert component, and the influence of TPS incorporation was studied in terms of tensile properties and crystallization kinetics. Tensile properties of the blends were affected by the addition of TPS particles, which reflects the incompatibility and lack of adhesion at the interface. The effect of TPS incorporation on the crystallization behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The significantly increased X c of PBAT biocomposites suggests that TPS can act as nucleating agent and can accelerate the crystallization rate of PBAT in all biocomposites. Such nucleating effect of TPS on PBAT is similar to that of polylactic acid (PLA), LLDPE, high density polyethylene, PCL, and poly(1,4‐dioxan‐2‐one) (PPDO)…”
Section: Resultsmentioning
confidence: 69%
“…The significantly increased X c of PBAT biocomposites suggests that TPS can act as nucleating agent and can accelerate the crystallization rate of PBAT in all biocomposites. Such nucleating effect of TPS on PBAT is similar to that of polylactic acid (PLA), LLDPE, high density polyethylene, PCL, and poly(1,4‐dioxan‐2‐one) (PPDO)…”
Section: Resultsmentioning
confidence: 69%
“…These new peaks show the formation of carboxyl and ester carbonyl bands for both treatments. The presence of a carbonyl peak in AA and SA confirmed that chemical linkages between ascorbic acid and acid anhydride and starch existed [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that all the six fillers studied acted as reinforcing fillers to increase the tensile strength of NR/HDPE blends and it may be due to the formation of interactions between filler and the NR/HDPE blend. Amorphous NR is incompatible with semi-crystalline HDPE 21 and hence, the NR dispersed phase in the HDPE matrix should tend to aggregate after mixing. However, it was reported 22 that the particulate fillers can act as solid barriers around the rubber domains preventing them from coalescence and facilitate to retain the well-dispersed rubber domains in the plastic matrix.…”
Section: Resultsmentioning
confidence: 99%